The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1177/00139165211014618
|View full text |Cite
|
Sign up to set email alerts
|

Nature Contact in the Carceral Workplace: Greenspace and Staff Sickness Absence in Prisons in England and Wales

Abstract: This paper demonstrates for the first time that prisons with a higher proportion of natural vegetation within their perimeter have lower levels of staff sickness absence. It makes three significant contributions. First, it extends studies of workplace nature contact into the un-researched carceral context. Second, whereas previous workplace nature contact studies have largely utilized single-site surveys, it presents national-level, statistically robust analysis. Third, it brings a novel new perspective to stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 40 publications
3
17
0
Order By: Relevance
“…Self-reported responses to nature contact in UK and Norwegian prisons revealed increased feelings of calm and ability to reflect (Moran and Turner, 2019;Moran, 2019). Similarly, a recent study of 326 male prisoners across three prisons in China identified a positive relationship between views of nature from their cells and self-reported well-being (Li et al, 2021) Recently, a set of our studies has examined the relationship between greenspace and well-being in the prison system of England and Wales (Moran et al, 2021a(Moran et al, , 2021b(Moran et al, , 2022a(Moran et al, , 2022b. Using publicly available data for a cross-section of prisons, these studies relate prison-level incidents of self-harm, violence amongst prisoners and violence towards staff to the percentage of greenspace of prison terrains and various prison characteristics (e.g.…”
Section: Greenspace and Well-being In Prisonsmentioning
confidence: 80%
See 1 more Smart Citation
“…Self-reported responses to nature contact in UK and Norwegian prisons revealed increased feelings of calm and ability to reflect (Moran and Turner, 2019;Moran, 2019). Similarly, a recent study of 326 male prisoners across three prisons in China identified a positive relationship between views of nature from their cells and self-reported well-being (Li et al, 2021) Recently, a set of our studies has examined the relationship between greenspace and well-being in the prison system of England and Wales (Moran et al, 2021a(Moran et al, , 2021b(Moran et al, , 2022a(Moran et al, , 2022b. Using publicly available data for a cross-section of prisons, these studies relate prison-level incidents of self-harm, violence amongst prisoners and violence towards staff to the percentage of greenspace of prison terrains and various prison characteristics (e.g.…”
Section: Greenspace and Well-being In Prisonsmentioning
confidence: 80%
“…Figure 1 shows how we envisage the various groups of factors to be associated with prisoner well-being. In Moran et al (2021aMoran et al ( , 2022aMoran et al ( , 2022b we focused on estimating the relationship between greenspace and inverse indicators of prisoner well-being in the form of self-harm and prison violence, while controlling for various prison characteristics. As such, these studies are based on estimating models that primarily relate the variation of well-being to how prisons differ according to factors related to prison management and deprivation.…”
Section: Methods and Datamentioning
confidence: 99%
“…Furthermore, the size of a prison’s population versus the actual building capacity will indicate whether buildings are under capacity, at normal capacity, or over capacity, which can also impact wellbeing. In England and Wales, the rate of overcrowding, rather than the size of a prison population, has been associated with increased offending and assault rates, increased recidivism rates (Farrington & Nuttall, 1980), and higher rates of staff sick leave (Moran et al, 2021). Prisons with certified normal occupancy in England and Wales reported increased scores on four healthy prison indicators including safety, respect, purposeful activity, and resettlement (Madoc-Jones et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, recent national studies from England and Wales found that in more than 80 public prisons, the mere presence of nature, defined as vegetated space within a prison’s perimeter walls, produced a significant negative effect on rates of staff sick leave and wellbeing among the incarcerated. Prisons with a greater percentage of vegetated space, regardless of prison building users’ ability to view or access it, reported lower levels of staff sick leave, self-harm among the incarcerated population, and violence both toward staff and among the incarcerated (Moran et al, 2020, 2021). Consequently, the authors call for the greening of all space within prison perimeters wherever possible.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation